Copper-Catalyzed Arylation of Alkenyl Aziridines via Three-Component Coupling Reaction involving Alkynes and Benzyne - Berti, Francesco; Crotti, Paolo; Cassano, Giulio; Pineschi, Mauro (Synlett, 2012)
Alkenyl aziridines can be successfully arylated in a three-component coupling triggered by in situ generated benzyne with a simple copper catalyst (CuI–PPh3), without the need of any palladium salts. The corresponding allylic amines can be obtained with good to high regioselectivity in mild reaction conditions with a variety of cyclic and acyclic alkenyl aziridines. A new domino reaction with ethyl propiolate to give tetrahydrophenanthridine was also found.
Keywords: arylation; copper catalysis; aziridine; terminal alkyne; benzyne